Immunization Update 2005: Stepping Forward - Noni E Macdonald (Canadian Journal of Infectious Diseases and Medical Microbiology, 2005)
This year marks a major step forward in improving access for all children and youth in Canada to the routine vaccines recommended by the National Advisory Committee on Immunization (Figure 1) (1). The disparity in vaccine access between have and have not regions noted previously (2,3) has been narrowed through the collaboration of the federal and provincial/territorial governments in the area of immunization (4). Unfortunately, harmonization of schedules across the country still remains a dream (Table 1). This lack of harmony continues to put children and youth who relocate at potential risk for missing out on a routine vaccine due to schedule timing differences. This is not a new problem (5) but one that is now more exaggerated due to the added variation in schedules and catch-up programs with the ?newer? vaccines (eg, varicella, conjugated pneumococcal and conjugated meningococcal vaccines) (Tables 1 and 2). Determining what a child or youth needs on arrival into a new region is often not an easy task.